Inflammation-induced changes in BKCa currents in cutaneous dorsal root ganglion neurons from the adult rat - Zhang Xiu-Lin; Mok Lee-Peng; Lee Kwan; Charbonnet Marcel; Gold Michael S (Molecular Pain, 2012)
Abstract Background Inflammation-induced sensitization of primary afferents is associated with a decrease in K+ current. However, the type of K+ current and basis for the decrease varies as a function of target of innervation. Because glabrous skin of the rat hindpaw is used often to assess changes in nociception in models of persistent pain, the purpose of the present study was to determine the type and extent to which K+ currents contribute to the inflammation-induced sensitization of cutaneous afferents. Acutely dissociated retrogradely labeled cutaneous dorsal root ganglion neurons from naïve and inflamed (3 days post complete Freund’s adjuvant injection) rats were studied with whole cell and perforated patch techniques. Results Inflammation-induced sensitization of small diameter cutaneous neurons was associated with an increase in action potential duration and rate of decay of the afterhyperpolarization. However, no changes in voltage-gated K+ currents were detected. In contrast, Ca2+ modulated iberiotoxin sensitive and paxilline sensitive K+ (BKCa) currents were significantly smaller in small diameter IB4+ neurons. This decrease in current was not associated with a detectable change in total protein levels of the BKCa channel α or β subunits. Single cell PCR analysis revealed a significant change in the pattern of expression of α subunit splice variants and β subunits that were consistent, at least in part, with inflammation-induced changes in the biophysical properties of BKCa currents in cutaneous neurons. Conclusions Results of this study provide additional support for the conclusion that it may be possible, if not necessary to selectively treat pain arising from specific body regions. Because a decrease in BKCa current appears to contribute to the inflammation-induced sensitization of cutaneous afferents, BKCa channel openers may be effective for the treatment of inflammatory pain.